Pharmaceutical calculations for the pharmacy technician - Lacher, Barbara E. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2007)
Intended for use in an introductory pharmacy technician calculations course, this book addresses the calculations that technicians encounter in retail, and also those necessary for compounding, IV, industry and areas where a pharmacy technician might be called upon because of the shortage of pharmacy professionals.
Fundamentals of calculations -- Systems of measure -- Interpretation of the prescription or medication order -- Equipment used in measuring -- Understanding drug labels -- Calculations of oral doses -- Calculations for pediatric doses -- Reducing and enlarging formulas -- Percentage, ratio strength, and other expressions of concentration -- Dilution and concentration -- Some calculations involving units, micrograms per milliliter, and other measures of potency -- Reconstituted solutions and intravenous admixtures -- Intravenous rate of flow calculations -- Contemporary compounding
Includes bibliographical references and index.
Keywords: PHARMACEUTICAL ARITHMETHIC